Caudillos, democracy, and constitutionalism in mid nineteenth-century Argentina. Issue 2 (3rd May 2020) - Zimmermann, Eduardo
ABSTRACT: Since the early years of Independence, through the failed constitutional projects of 1819 and 1826, and culminating in the 1853 Constitutional Convention of 1853, the River Plate provinces witnessed a varied number of juridical and political debates on the status of democracy and its different meanings: as an expression of social forces announcing the dawn of a new form of social organization; as an ideal of representative government that was to accompany the transition from monarchical to republican forms of government; and as a number of possible electoral regimes and technical solutions to the problem of representation. On the other hand, constitutionalism promised not only a way of structuring the new governments but also the adoption of the idea of individual rights as an ideological foundation for the new liberal regimes, and a project to transcend the inorganic rule of provincial caudillos. This paper explores the different languages in which nineteenth-century Argentine constitutionalism was shaped, through an analysis of political and constitutional debates and the writings of many of the actors of the period, taking into account the ways in which the conflictive context of independence, civil wars, national unification, and state building delineated a particular conception of liberal constitutionalism.